Republic of Congo : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes poverty and inequalities in Congo and the public expenditure priorities for inclusive growth. Congo's outlook of more limited fiscal space, in view of the need for fiscal consolidation, makes it all the more important that public expenditure programs maximize their impact. This paper highlights the scope to reorient public expenditure policies to better address poverty and inequality. Based on the recent World Bank Public Expenditure Management and Financial Accountability Review, the analysis notes that recent economic growth has only translated into relatively modest reductions in poverty. Against this background, recommendations are developed that can help guide future budget allocations with a view to promoting inclusion and reducing inequality.